2010
DOI: 10.1002/jcp.22225
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of osteoblast and osteoclast functions by FGF‐6

Abstract: Fibroblast growth factor-6 (FGF-6) is known to be the key ligand for fibroblast growth factor receptor 4 (FGFR4) during muscle regeneration but its role in bone has yet to be verified. FGFR signaling is known to be important in the initiation and regulation of osteogenesis, so in this study the actions of FGF-6 on human osteoblasts and osteoclasts were investigated. Human primary osteoblasts (hOB) were used to study the effect of FGF-6 on proliferation (by ATP quantification), signal transduction (by ERK and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 27 publications
0
24
0
3
Order By: Relevance
“…FGF18 can also induce osteoclast formation and function indirectly through stimulating receptor activator of the nuclear factor-κB ligand (RANKL) and cyclooxygenase-2 expression in osteoblasts (Shimoaka et al 2002). Another study showed that FGF6 increased the formation and resorbing activity of human primary mature osteoclasts in vitro (Bosetti et al 2010), whereas FGF8a inhibited osteoclastogenesis, but not osteoclast function, in mouse bone marrow cultures.…”
Section: Fgf Signaling In Osteoclastsmentioning
confidence: 99%
“…FGF18 can also induce osteoclast formation and function indirectly through stimulating receptor activator of the nuclear factor-κB ligand (RANKL) and cyclooxygenase-2 expression in osteoblasts (Shimoaka et al 2002). Another study showed that FGF6 increased the formation and resorbing activity of human primary mature osteoclasts in vitro (Bosetti et al 2010), whereas FGF8a inhibited osteoclastogenesis, but not osteoclast function, in mouse bone marrow cultures.…”
Section: Fgf Signaling In Osteoclastsmentioning
confidence: 99%
“…Mutations in P2RX7 gene have been associated with low lumbar spine BMD, and accelerated bone loss in post-menopausal women (18). FGFR signaling is known to be important in the initiation and regulation of osteogenesis, and the IIIc alternative of Fgfr2 is a positive regulator of bone formation, affecting mainly the osteoblast (19, 20). SYK(-/-) progenitors are similarly defective in osteoclast development and bone resorption (21).…”
Section: Resultsmentioning
confidence: 99%
“…Bone calcein labeling has been used earlier to assess the histomorphometry of remolded bones in vivo [42]. Calcein staining has also recently been introduced to examine and quantify osteoblast differentiation and the matrix mineralization of human primary osteoblasts [43]. Further, Calcein, also known as fluorexon or fluorescein complex, is a fluorescent dye with excitation and emission wavelength of 495/515 nm, respectively.…”
Section: Discussionmentioning
confidence: 99%